Extraordinary diffusion in Co/Cu grain boundaries. (May 2015) - Nakano, Hiromi; Yuasa, Motohiro; Miyamoto, Hiroyuki; Miyazawa, Naoki; Mabuchi, Mamoru
Abstract : Usually, Cu atoms hardly diffuse in Co because of the very low solid solubility limit. However, this letter shows by transmission electron microscopy that extraordinary diffusion of Cu in the Co phase occurred in Co/Cu bicrystal fabricated by diffusion joining and that many dislocations were found in the Co phase. First-principles calculations suggested that the extraordinary diffusion of Cu in Co is related to the movement of dislocations which Cu atoms adhere to.